2016
DOI: 10.1039/c6sm01033d
|View full text |Cite
|
Sign up to set email alerts
|

Critical behaviour in the nonlinear elastic response of hydrogels

Abstract: In this paper we study the elastic response of synthetic hydrogels to an applied shear stress. The hydrogels studied here have previously been shown to mimic the behaviour of biopolymer networks when they are sufficiently far above the gel point. We show that near the gel point they exhibit an elastic response that is consistent with the predicted critical behaviour of networks near or below the isostatic point of marginal stability. This point separates rigid and floppy states, distinguished by the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The semiflexible synthetic networks of Ref. [49], which have been shown to exhibit critical behavior in their response to stress [50,51], have a value of X ∼ 10 −4 -10 −3 in water, well below the peak value and close to where we expect stiffer networks with low α c . For biopolymer networks consisting of neurofilaments, for example, we estimate X ∼ 10 −2 -10 −1 in water [49], which should show some of the effects of hydrodynamic interactions [see Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The semiflexible synthetic networks of Ref. [49], which have been shown to exhibit critical behavior in their response to stress [50,51], have a value of X ∼ 10 −4 -10 −3 in water, well below the peak value and close to where we expect stiffer networks with low α c . For biopolymer networks consisting of neurofilaments, for example, we estimate X ∼ 10 −2 -10 −1 in water [49], which should show some of the effects of hydrodynamic interactions [see Fig.…”
Section: Resultsmentioning
confidence: 71%
“…While we have used Hookean springs as model filament's in this work, semiflexible polymers, which make up such real networks, exhibit a more complex response to stress: Hookean springs show only a linear force-extension response, while semiflexible polymers show an initial force extension, followed by a nonlinear stiffening as it is stretched towards its contour length. This effect has been shown to give rise to increasingly complex critical behavior in the stress response of marginal networks [50,51], and an open question we aim to address in future work is how using more realistic model filaments will effect the critical response found here.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…So far, marginal materials have been described only in theory and by simulations 17 and no experimental (bio)polymer network has validated these predictions yet. The PIC gels are the first materials that display some of the predicted characteristics 25 . An additional prediction is a vanishing σ c (also experimentally observed in the PIC hydrogel, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, we described a synthetic ECM‐mimicking system based on a helical ethylene‐glycol‐functionalized polyisocyanopeptide (PIC, Figure S3, Supporting Information) and found that this gel closely resembles the mechanical properties of naturally occurring polymer networks. [ 20–22 ] This synthetic PIC polymer forms soft thermoresponsive heat‐set gels with rheological properties that closely mimic the strain‐stiffening behavior of biogels, [ 23–25 ] such as actin, [ 26 ] collagen, and intermediate filaments. [ 27 ] The benefit of PIC, as a well‐defined synthetic material, is that complex rheological and functional properties of the PIC gels can be easily controlled and tuned to specific needs and applications.…”
Section: Polymer Salt Concentration [M] Polymer Concentration [Mg Ml−mentioning
confidence: 99%